Effect of dietary plant secondary metabolites on rumen fermentation and microbial community: A review - Banakar, P S; Sarkar, Srobana; Tyagi, Bhawna; Vinay, V V; Chugh, Timmi; Kumar, Sachin; Tyagi, Nitin; Tyagi, A K (Indian Journal of Animal Nutrition, 2019)
Plants are a significant source for the discovery of novel medicinal products and secondary metabolites are a distinctive source of pharmaceutical food additives, flavours and other industrial values. These plant secondary metabolites are found to manipulate rumen fermentation process by altering the population of microbial community. Changes in microbial population has further aided in limiting the biohydrogenation process of fatty acids and production of methane. Biohydrgenation of the ingested fatty acids results in saturated fatty acids produced at the cost of unsaturated fatty acids. Animal science advocates are trying various feasible approaches to influence ruminal biohydrogenation processes to achieve ruminant-derived products with reduced saturated fatty quantity, which would be of significant value to the wellness of consumers. Dose dependent action of plant secondary metabolites on rumen microbes is not completely investigated. However, it is more suitable to use phytochemicals as modulators of ruminal biohydrogenation under economic and social development than most other supplements, such as oil or oil-rich grains.